Lessons from Singapore's national weight management program, Lose To Win. (24th May 2017) - Vasquez, Kathryn; Malhotra, Rahul; Østbye, Truls; Low, Wilson; Chan, Mei Fen; Chew, Ling; Ling, Annie
Summary: The prevalence of overweight and obesity in Singapore is lower than in most countries, but it is increasing. There is evidence health complications may appear at lower weights among Asians. We describe the evolution of a national weight management program [Lose To Win (LTW)] organized by the Singapore Health Promotion Board from 2009 to 2013. LTW is a 12-week program comprising nutrition education, physical activity and mental wellbeing sessions and interim assessments. Individuals aged 18–69 years with a body mass index (BMI) between 23 and 37.4 kg/m 2 were included. Primary outcomes were change in weight and BMI from baseline to end of 12-weeks. Effectiveness of the weight loss program was assessed using non-randomized control group (delayed intervention) during LTW 2010 and 2012. LTW 2009 enrolled 285 participants from 72 worksites. LTW 2010, expanded to the community, enrolling 952 participants (641 community-based and 311 workplace-based). In LTW 2012 and 2013, 959 and 1412 participants, respectively, were recruited from the community only. Completion rates of the 12-week program varied from 49 to 88%. Average weight loss ranged from 1.3 to 3.6 kg. For rounds including a control group, weight loss was higher in the intervention than in the control group. Competition and incentives were important motivators for participation. The LTW program was well-received and effective in producing short-term weight loss. Enhancements will be done to reinforce success factors in subsequent rounds to boost participation and follow-up rates and to ensure long-term sustainability.